Robot-Assisted Middle Ear Endoscopic Surgery: Preliminary Results on 37 Patients - Veleur, Marine; Lahlou, Ghizlene; Torres, Renato; Daoudi, Hannah; Mosnier, Isabelle; Ferrary, Evelyne; Sterkers, Olivier; Nguyen, Yann (Frontiers in Surgery, 2021)
Background: Endoscopy during middle ear surgery is advantageous for better exploration of middle ear structures. However, using an endoscope has some weaknesses as surgical gestures are performed with one hand. This may trouble surgeons accustomed to using two-handed surgery, and may affect accuracy. A robot-based holder may combine the benefits from endoscopic exposure with a two-handed technique. The purpose of this study was to assess the safety and value of an endoscope held by a teleoperated system. Patients and Methods: A case series of 37 consecutive patients operated using endoscopic exposure with robot-based assistance was analyzed retrospectively. The RobOtol® system (Collin, France) was teleoperated as an endoscope holder in combination with a microscope. The following data were collected: patient characteristics, aetiology, procedure type, complications, mean air and bone conduction thresholds, and speech performance at 3 months postoperatively. Patients had type I (myringoplasty), II (partial ossiculoplasty) and III (total ossiculoplasty) tympanoplasties in 15, 14, and 4 cases, respectively. Three patients had partial petrosectomies for cholesteatomas extending to the petrous apex. Finally, one case underwent resection of a tympanic paraganglioma. Ambulatory procedures were performed in 25 of the 37 patients (68%). Results: Complete healing with no perforation of the tympanic membrane was noted postoperatively in all patients. No complications relating to robotic manipulation occurred during surgery or postoperatively. The mean air conduction gain was 3.8±12.6 dB for type I (n=15), 7.9±11.4 dB for type II (n=14), and –0.9±10.8 for type III tympanoplasties (n=4), and the postoperative air-bone conduction gap was 13.8 ± 13.3 dB for type I, 19.7±11.7 dB for type II and 31.6±13.0 dB for type III tympanoplasty. They was no relapse of cholesteatoma or paraganglioma during the short follow-up period (less than 1 year). Conclusion: This study indicates that robot-assisted endoscopy is a safe and trustworthy tool for several categories of middle ear procedures. It combines the benefits of endoscopic exposure with a two-handed technique in middle ear surgery. It can be used as a standalone tool for pathology limited to the middle ear cleft or in combination with a microscope in lesions extending to the mastoid or petrous apex.